2005
DOI: 10.17221/3556-pse
|View full text |Cite
|
Sign up to set email alerts
|

The antioxidative response of two tomato species with different drought tolerances as a result of drought and cadmium stress combinations

Abstract: The effects of drought, cadmium (Cd) and drought-Cd combinations on antioxidant compounds, antioxidant enzymes and shoot growth were investigated for drought tolerant [Lycopersicon peruvianum (L.) Mill.] and sensitive of (Lycopersicon esculentum Mill. cv. Lukullus) tomato species. Drought-Cd combinations significantly decreased shoot growth in both species (P < 0.01), drought stress also decreased shoot growth in drought sensitive L. esculentum. Cd was accumulated higher in the roots of drought sensitive L. es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(30 citation statements)
references
References 34 publications
2
27
0
1
Order By: Relevance
“…It is evident from literature data that different plant species differ considerably in their AOE activities in response to water deficit (Moran et al 1994, Zhang and Kirkham 1996, Ünyayar et al 2005. In this work we observed that activities of AOE in WT leaves were almost not affected during water deficit in contrast to roots where APX and GR activities increased upon stress.…”
Section: Discussionsupporting
confidence: 55%
“…It is evident from literature data that different plant species differ considerably in their AOE activities in response to water deficit (Moran et al 1994, Zhang and Kirkham 1996, Ünyayar et al 2005. In this work we observed that activities of AOE in WT leaves were almost not affected during water deficit in contrast to roots where APX and GR activities increased upon stress.…”
Section: Discussionsupporting
confidence: 55%
“…Carotenoid was more sensitive towards stress as compared with chlorophyll in respective treatments. Single and combined stress treatment exhibited negative impact on carotenoid content of wheat seedling (Ünyayar et al, 2005;Mishra and Agrawal, 2006). The decrease in carotenoid content is harmful to chlorophyll because carotenoid protects chlorophyll from photooxidative destruction (Middleton and Teramura, 1993).…”
Section: Resultsmentioning
confidence: 99%
“…Production of reactive oxygen species (ROS) scavengers is an important device to increase tolerance against oxidative stress (Sairam et al, 1998). Superoxide dismutase (SOD), catalase (CAT), ascorbate peroxidase (APX) and guaiacol peroxidase (GPX) are antioxidant enzymes which detoxify ROS (Rubio et al, 2002;Ünyayar et al, 2005) and protect crop plants in oxidative stress. Yadav and Singh (2013) reported that BA at 0.5, 1.0 and 1.5 mM concentrations exhibited toxic effects on crop plants.…”
Section: Introductionmentioning
confidence: 99%